The Effect of Entry Requirement for Civil Engineering Student Performance - Ab. Ghani, Amran; Mohamed, Rozlini (Journal of Science and Technology, 2017)
This study presents the performance analysis of Civil Engineering student for Civil Engineering subject and its relation to the entry requirement before admission to Politeknik Port Dickson, Negeri Sembilan. The objective of this research is to analyse the effect of entry requirements toward student performance for subject Mechanic Structure. The minimum entry requirement to polytechnic is compulsory to pass English language, Malay Language and History subject. Also, Mathematic and another one subject must be credit. In this research, only four subjects are involved which is English, Bahasa Malaysia, History and Mathematic subject. The research sample is 39 students that randomly choose among the first year second semester diploma student that already taken this subject. In this research, questionnaire is used as tool to collect the assessment result of Mechanic Structure subject. The student assessment can be divided into two methods, theory and practical which is 50% and 50% of the total assessment for theory and practical, respectively. The implementation of teaching and learning in former secondary school is different approach with teaching and learning in polytechnic. In polytechnic the teaching method is more to student-centered approach. This approach needs more effort from student comparing lecturer. Therefore, independent study is required to meet the purpose in polytechnic. The students results of Mechanic Structure course have been analyse. The results indicate moderate correlation between students’ performance and entry admission before admission to Politeknik Port Dickson.